2020
DOI: 10.1111/ggr.12367
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of U, Pb and Rare Earth Elements in Calcite through Crystallisation from Amorphous Calcium Carbonate: Simple Preparation of Reference Materials for Microanalysis

Abstract: Uncertainty for elemental and isotopic measurements in calcite by LA‐ICP‐MS is largely controlled by the homogeneity of the reference materials (RMs) used for calibration and validation. In order to produce calcite RMs with homogeneous elemental and isotopic compositions, we incorporated elements including U, Pb and rare earth elements into calcite through heat‐ and pressure‐induced crystallisation from amorphous calcium carbonate that was precipitated from element‐doped reagent solution. X‐ray absorption spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Matsunuma et al showed that pressure-induced crystallization of ACC is more efficient for doping incompatible elements into crystals than crystallization in supersaturated solutions. Recently, calcite incorporating large amounts of incompatible elements such as Sr 2+ , Ba 2+ , and U 6+ was synthesized by heat-induced crystallization of element-doped ACC. , The dolomitization by a solid-phase reaction from ACMC may also facilitate the synthesis of element-doped dolomite.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Matsunuma et al showed that pressure-induced crystallization of ACC is more efficient for doping incompatible elements into crystals than crystallization in supersaturated solutions. Recently, calcite incorporating large amounts of incompatible elements such as Sr 2+ , Ba 2+ , and U 6+ was synthesized by heat-induced crystallization of element-doped ACC. , The dolomitization by a solid-phase reaction from ACMC may also facilitate the synthesis of element-doped dolomite.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, calcite incorporating large amounts of incompatible elements such as Sr 2+ , Ba 2+ , and U 6+ was synthesized by heatinduced crystallization of element-doped ACC. 44,45 The dolomitization by a solid-phase reaction from ACMC may also facilitate the synthesis of element-doped dolomite.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The process of ‘additive manufacturing’ clearly has great potential in the production of matrix-matched RMs. The incorporation of Pb, REEs and U into calcite involved 207 heat- and pressure-induced crystallisation from amorphous calcium carbonate that had been precipitated from an element-doped reagent solution. The doped elements in the resulting calcite RMs were homogenously distributed (<12%, 2RSD).…”
Section: Analysis Of Geological Materialsmentioning
confidence: 99%